SCHOOL ATTACKS, SCHOOL CLOSURES AND THEIR IMPACT ON EDUCATION IN NIGERIA - Edinoh , Kingsley; Asemota, Ruth; Ifeobu-Emeanu, Uchenna Victoria (Multi-Disciplinary Research and Development Journals Int'l, 2025)
The paper discussed School Attacks, School Closures and their impact on Education in Nigeria. Secondary data were used in the study. The data were collected from both print and online publications. Content analysis was used to analyze the selection of literature for the study. The paper concluded that School attacks and schools’ closures in Nigeria as a result of banditry and insurgencies have led to disruption of learning, increased out-of-school rates, psychosocial trauma, and insecurity widening educational inequalities and long-term human-capital loss in the Nigerian educational system. Based on these findings, the study recommended that government must ensure that security measures are implemented to guarantee the safety of students and teachers. This includes providing adequate protection for schools and increasing patrols in vulnerable areas. Government should focus on rebuilding and reopening schools that have been attacked or closed. This will not only provide students with a safe learning environment but also send a message of resilience and hope. Government must increase efforts to address the root causes of school attacks and closures. This includes addressing issues of poverty, inequality, and religious extremism, which contribute to these problems. By tackling these underlying issues, there is a better chance of ensuring a safe and stable environment for education in Nigeria.